Some homological properties of Jordan plane (2018)
The Jordan plane can be seen as a quotient algebra, as a graded Ore extension and as a graded skew PBW extension. Using these interpretations, it is proved that the Jordan plane is an Artin-Schelter regular algebra and a skew Calabi-Yau algebra, in addition its Nakayama automorphism is explicitly calculated.